2017
DOI: 10.4025/actasciagron.v39i4.35420
|View full text |Cite
|
Sign up to set email alerts
|

<b>Aspects of the sensorial quality and nutraceuticals of <i>Plinia cauliflora</i> fruits

Abstract: ABSTRACT. Nationally known in Brazil, the jabuticabeira or jabuticaba tree produces fruits of wide commercial acceptance. However, little use of jabuticaba in commercial orchards and large genetic erosion of jabuticaba caused by human activities in its habitats have been historically observed. Thus, the goal of this study was to characterize fruits of the jabuticaba tree (Plinia cauliflora) in a forest fragment maintained in southwestern Paraná State in an attempt to identify trees with superior fruits for fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
4
0
5
Order By: Relevance
“…It was reported that this fruit has up to 58.1 mg/100 g of anthocyanins in fresh whole fruit [6] and 298.8-426.3 mg/100 g in peel, which agrees with the values observed in the present work. In the pulp, they reported lower values, 0.071-2.024 mg/100 g [8], than what was observed in pulps and seeds, which are used for the preparation of handmade marmalade in Paraguay. The values obtained in the pulp and seed were higher than those reported by other authors for Plinia cauliflora pulp in Brazil (32.4 mg GAE/100 g), and lower than the values reported in fruit peel harvested in Minas Gerais, Brazil [8].…”
Section: Anthocyanins and Total Phenol Content In Fruitsmentioning
confidence: 68%
See 1 more Smart Citation
“…It was reported that this fruit has up to 58.1 mg/100 g of anthocyanins in fresh whole fruit [6] and 298.8-426.3 mg/100 g in peel, which agrees with the values observed in the present work. In the pulp, they reported lower values, 0.071-2.024 mg/100 g [8], than what was observed in pulps and seeds, which are used for the preparation of handmade marmalade in Paraguay. The values obtained in the pulp and seed were higher than those reported by other authors for Plinia cauliflora pulp in Brazil (32.4 mg GAE/100 g), and lower than the values reported in fruit peel harvested in Minas Gerais, Brazil [8].…”
Section: Anthocyanins and Total Phenol Content In Fruitsmentioning
confidence: 68%
“…This result showed that the analyzed fruits harvested in Paraguay are smaller than those of synonymous species fruits in the state of Paraná, Brazil. These fruits weigh between 6.4 and 11.4 g and their diameter is near to 2.65 cm [7,8]. The pH values in the fruits are acidic and differ from the results reported by other authors (pH = 3.6-4.3) for the synonymous species of Plinia peruviana harvested in Brazil [7] P. cauliflora and P. trunciflora.…”
Section: Yvapurũ Fruit Characteristicsmentioning
confidence: 83%
“…Jabuticaba (Myrciaria jabuticaba (Vell) Berg) is a fruit species native to Brazil, belonging to the Myrtaceae family. The lack of knowledge about production results in the low use of jabuticaba, which contributes to its genetic erosion (WAGNER JÚNIOR et al, 2017). However, it is a fruit that has high potential for food use.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, há pesquisas que verificaram valores variando de 6 a 8 gramas para massa dos frutos de jabuticabeira (Wagner Junior et al, 2017;. O período de deficiência hídrica na época do crescimento dos frutos nas condições do presente estudo, pode ter favorecido a menor massa média dos mesmos (Chitarra e Chitarra, 2005).…”
Section: Resultsunclassified
“…O período da antese a colheita dos frutos pode variar de acordo com as condições climáticas, cultivares e época do ano (Cavichioli et al, 2006). Segundo Araújos et al Araújos et al, 2010;Wagner Junior et al, 2017) para jabuticabeiras.…”
Section: Methodsunclassified